Prescribing opioid analgesics for chronic non-malignant pain in general practice - a survey of attitudes and practice - Blake, Holly; Leighton, Paul; van der Walt, Gerrie; Ravenscroft, Andrew (SAGE, 2015)
Background: This study replicates a previous postal survey of general practitioners (GPs) to explore whether attitudes to opioid prescribing have changed at a time when the number of opioid prescriptions issued in primary care has increased.